Association between hepatic steatosis and serum liver enzyme levels with atrial fibrillation in the general population: The Study of Health in Pomerania (SHIP). (February 2016) - Markus, Marcello Ricardo Paulista; Meffert, Peter J.; Baumeister, Sebastian Edgar; Lieb, Wolfgang; Siewert, Ulrike; Schipf, Sabine; Koch, Manja; Kors, Jan A.; Felix, Stephan Burkhard; Dörr, Marcus; Targher, Giovanni; Völzke, Henry
Abstract: Background: Hepatic steatosis (HS) affects up to 35% of adults in the general population. Atrial fibrillation (AF) is the most prevalent sustained arrhythmia and has a substantial impact on healthcare costs. We analyzed cross-sectional associations of HS and serum liver enzyme levels with prevalent AF in a general population sample. Methods: We analyzed data from 3090 women and men, aged 20–81 years, from the population-based Study of Health in Pomerania. HS was determined by ultrasonography. Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyltranspeptidase (GGT) were measured photometrically. AF was determined by automatic electrocardiographic analysis software. Results: The prevalences of HS and AF were 30.3% and 1.49%, respectively. ALT, AST and GGT showed a positive linear association with the risk of prevalent AF, after multivariable adjustment. The adjusted odds ratios for AF per 1-standard deviation increment in log-transformed serum liver enzyme levels were 1.65 (95% confidence interval [CI]: 1.16 to 2.35; p = 0.006) for ALT, 1.47 (95%CI: 1.07 to 2.02; p = 0.017) for AST and 2.17 (95%CI: 1.64 to 2.87; p < 0.001) for GGT. In contrast, ultrasonographic HS was not associated with AF. Conclusions: Our findings indicate that moderately elevated serum liver enzymes, but not sonographic liver hyperechogenicity, were associated with increased AF prevalence in the general adult population. The hepatic release of increased levels of serum liver enzymes might be accompanied by higher levels of pro-inflammatory, pro-coagulant and pro-fibronogenic mediators that might lead to structural and electrical remodeling of the atrium resulting in the development and persistence of AF. Highlights: The prevalences of hepatic steatosis and atrial fibrillation were 30.3% and 1.49. Mild to moderate elevations of serum liver transaminases were associated with AF. HS determined by ultrasonography, did not show an association with AF.